The impact of lemon pectin characteristics on TLR activation and T84 intestinal epithelial cell barrier function. (April 2016) - Vogt, Leonie M.; Sahasrabudhe, Neha M.; Ramasamy, Uttara; Meyer, Diederick; Pullens, Gerdie; Faas, Marijke M.; Venema, Koen; Schols, Henk A.; de Vos, Paul
Highlights: Stimulation with lemon pectins induces activation of TLR2, TLR4 and NF-κB. An intact pectin backbone is essential for TLR activation. Degree of methyl esterification of the backbone determines activation strength. Lemon pectins demonstrate strong protection on epithelial cell barrier. Lemon pectins are thus promising ingredients for health improving functional foods. Abstract: Sufficient dietary fibre intake reduces the risk of several diseases, but the mechanisms linking fibre structure and health effects remain unclear. To analyse the influence of the amount of methyl groups esterified to the backbone, lemon pectins of different degrees of methyl esterification (30, 56, and 74DM) were studied for immune receptor activating potential and epithelial barrier protection. In reporter assays, the pectins demonstrated TLR/MyD88 dependent activation of NF-κB/AP-1, which increased with increasing pectin DM. To analyse the importance of backbone structure, the pectins were enzymatically digested into oligomers, which abrogated TLR activating potential. The 30 and 74DM pectins induced strong protection of the epithelial barrier measured by T84 transepithelial electrical resistance (TEER). These results indicate that activation of immune cells by lemon pectins is TLR dependent, and the intact polymer backbone is indispensable for activation. In addition, DM is a determining factor in activating potential and epithelial barrier protective effects.